Biological characterization of Tomato leaf curl New Delhi virus from Spain. (11th August 2016) - Ruiz, L.; Simon, A.; Velasco, L.; Janssen, D.
Abstract : Tomato leaf curl New Delhi virus (ToLCNDV; family Geminiviridae, genus Begomovirus ) is an emerging virus in horticulture crops in Asia, and has recently been introduced in Spain, Tunisia and Italy. No betasatellite DNA was detected in infected tomato and zucchini squash samples from Spain, and agroinoculated viral DNA‐A and DNA‐B were sufficient to reproduce symptoms in plants of both crop species. Infected tomato and zucchini squash plants also served as inoculum sources for efficient transmission either mechanically or using Bemisia tabaci whiteflies. Cucumber, melon, watermelon, zucchini squash, tomato, eggplant and pepper, but not common bean, were readily infected using viruliferous whiteflies and expressed symptoms 8–15 days post‐inoculation. New full‐length sequences from zucchini squash and tomato indicated a high genetic homogeneity (>99% sequence identity) in the ToLCNDV populations in Spain, pointing to a single recent introduction event.